FACTORS DETERMINING BANK LOAN APPROVAL AS SOURCE OF FINANCING FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSME) IN JAKARTA - Ekadjaja, Margarita (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2018)
In running business, the owners of Micro, Small, and Medium Enterprises (MSME) have main weaknesses, in which they do not conduct good accounting system or financial records, thus creating difficulties in developing analysis for future business planning. Most of MSME owners run their business by relying on instincts, while business analysis and accounting system are necessary when they apply for bank loan.The aim of this study is to reveal some variables of MSME that become the determinants of their bank loans approval. These variables are: Business Age since Establishment, Total Assets Turnover, Owner’s Total Assets, Credit Duration, Owner’s Education Level, Good Relationship with the Bank, Collateral Amount, and Loan Repayment Criteria. The samples of this study were taken from entrepreneurs selling clothes and apparels in Tanah Abang by conducting direct interview and fulfilling the questionnaire. The questionnaire consists of three major parts, which are business owner’s profile, credit analysis, and evaluation on simple financial report. This study uses logistic regression method, in which there is only one dependant variable with dummy 1-0 (Bank Loan Approval, granted = 1 and rejected = 0) along with eight independent variables.This study concludes that Business Age since Establishment, Total Assets Turnover, Owner’s Education Level, Collateral Amount, and Loan Repayment Criteria, have positive and significant effects on Bank Loan Approval. Meanwhile, Owner’s Total Assets, Credit Duration, and Good Relationship with the Bank do not affect Bank Loan Approval significantly.Keywords: MSME, bank loan approval, logistic regression